KINERJA PEGAWAI DI SEKRETARIAT PEMERINTAH DAERAH KABUPATEN KEPULAUAN ANAMBAS PROVINSI KEPULAUAN RIAU - Uray Dien Sutrisni (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article is motivated by the employees performance in the Local Government Secretariat Islands District Anambas is still not optimal. Based on this phenomenon, this study focused on the employees performance with aspects; productivity, responsiveness, responbilitas,  services quality, accountability of employees. The results showed that employee productivity is low, responsiveness still not optimal, and employee responsibility, service quality, and accountability is low. Keywords: employee performance